Indian Subcontinent’s First Proximal Forearm Level Double Upper Extremity Transplantation - Sharma, Mohit; Iyer, Subramania; Purushottaman, Kishore; Vijayaraghavan, Sundeep; Matthew, Jimmy; Dudipala, Raghuveer Reddy; Ramu, Janarthanan; Paul, Jerry; Rajan, Sunil; Anwar; Meera; Dhruvan; Arun; Arjun; Verma, Vishak; Chaudary, Ashish; Dhake, Swapnil; Omkumar, Akshay; Kapahtia, Radhika; Sharma, Dimpy; Maharaja, Nirav (Indian Journal of Plastic Surgery, 2019)
Introduction Vascularized composite allotransplantation (VCA) has added another step to the reconstructive ladder, leading to a paradigm shift in the approach toward management of cases of upper limb amputations. In this article, we discuss in detail the technical aspects of proximal forearm level transplantation, as well as the immediate posttransplant monitoring and immunosuppression protocols.Materials and Methods A 24-year-old male victim of an electric injury presented with a bilateral proximal forearm level amputation. After the mandatory preoperative psychiatric and immunological evaluation, the patient underwent a proximal forearm level double upper extremity transplantation. He was then put on a stringent immunosuppression and physical rehabilitative regime.Discussion Conceptually, the proximal forearm level transplantation is significantly different from distal forearm level transplant. This transplant “reestablishes” the “donor extremity length,” maintains the normal functional length of the donor muscles, and the functional return happens only after the newly transplanted donor muscles are reinnervated over a period of time.Conclusion As the sequence of surgical repair and associated decision making could be quite confusing for this level of transplantation, it is highly advisable to do mock cadaver surgical dissections in order to standardize the procedure and make the team familiar with it.
Keywords: proximal forearm transplantation; hand transplantation; hand transplantation in Indian sub continent; bilateral upper limb transplantation